Perbandingan Penggunaan Bit Steganografi Metode Least Significant Bit (LSB) m-bit pada Citra Digital - Amini, Safrina; Hardjianto, Mardi; Dewi Kusumaningsih (Jurnal Ticom: Technology of Information and Communication, 2025)
Steganography is an information hiding technique that aims to maintain confidentiality by inserting secret information into digital media, such as images, audio, or video, without revealing the existence of the message. One of the widely used steganography methods is Least Significant Bit (LSB). The limitation of this method is that the number of messages that can be hidden is very small. This is because if the message is too large, the media containing it will change clearly. This can arouse people's suspicion. The LSB method has several variants, one of which is the m-bit LSB. The value of m indicates the number of bits that can be used to store information in one byte of storage media. In this research, we look for the maximum m value that can be used so that the image that has been inserted with information (stego image) still has good quality. The test results obtained PSNR values ​​for m from one to three are 46.36, 39.87, and 33.31. These results indicate that the image still has good quality. Testing with an m value of 4, produced a PSNR value of 23.23, which means the image has quite good quality. The image quality will look bad if using m values ​​of 5 and 6. The resulting PSNR are 21.17 and 15.46.